2022
DOI: 10.3390/rs14215465
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis between Sea Surface Salinity Derived from SMOS Satellite Retrievals and in Situ Measurements

Abstract: Validating Sea Surface Salinity (SSS) data has become a key component of the Soil Moisture Ocean Salinity (SMOS) satellite mission. In this study, the gridded SMOS SSS products are compared with in situ SSS data from analyzed products, a ship-based thermosalinograph and a tropical moored buoy array. The comparison was conducted at different spatial and temporal scales. A regional comparison in the Baltic Sea shows that SMOS slightly underestimates the mean SSS values. The influence of river discharge overrides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…The ISAS database has been used for SL, temperature/heat content and salinity studies in many oceanic regions (Germineaud et al., 2023; Hasson et al., 2014; Hernandez et al., 2014; Kolodziejczyk et al., 2019; Llovel et al., 2022; H. Wang et al., 2022) and has shown similar performance to other commonly used databases such as the Roemmich–Gilson Argo climatology (e.g., Germineaud et al., 2023). In addition to the T and S analyzed fields, the ISAS20 provides the analyzed variance and the normalized analyzed variance, the so‐called PCTVAR (percentage of the a priori variance), which basically depends on the data sampling, on the correlation scales and on the measurement errors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ISAS database has been used for SL, temperature/heat content and salinity studies in many oceanic regions (Germineaud et al., 2023; Hasson et al., 2014; Hernandez et al., 2014; Kolodziejczyk et al., 2019; Llovel et al., 2022; H. Wang et al., 2022) and has shown similar performance to other commonly used databases such as the Roemmich–Gilson Argo climatology (e.g., Germineaud et al., 2023). In addition to the T and S analyzed fields, the ISAS20 provides the analyzed variance and the normalized analyzed variance, the so‐called PCTVAR (percentage of the a priori variance), which basically depends on the data sampling, on the correlation scales and on the measurement errors.…”
Section: Methodsmentioning
confidence: 99%
“…The ISAS database has been used for SL, temperature/heat content and salinity studies in many oceanic regions (Germineaud et al, 2023;Hasson et al, 2014;Hernandez et al, 2014;Kolodziejczyk et al, 2019;Llovel et al, 2022;H. Wang et al, 2022) and has shown similar performance to other commonly used databases such as the Roemmich-Gilson Argo climatology (e.g., Germineaud et al, 2023).…”
Section: Temperature and Salinity Datamentioning
confidence: 99%
“…Where RMSE and MAE are the Root Mean Square Error and the Mean Absolute Error [59,60], and their calculation equations are as follows:…”
Section: Deep Neural Network Modelmentioning
confidence: 99%